Amyloid precursor protein induces reactive astrogliosis - Velezmoro Jauregui, Gretsen; Vukić, Dragana; Onyango, Isaac G; Arias, Carlos; Novotný, Jan S; Texlová, Kateřina; Wang, Shanshan; Kovačovicova, Kristina Locker; Polakova, Natalie; Zelinkova, Jana; Čarna, Maria; Lacovich, Valentina; et al. (Acta physiologica, 2024)
AIM: Astrocytes respond to stressors by acquiring a reactive state characterized by changes in their morphology and function. Molecules underlying reactive astrogliosis, however, remain largely unknown. Given that several studies observed increase in the Amyloid Precursor Protein (APP) in reactive astrocytes, we here test whether APP plays a role in reactive astrogliosis. METHODS: We investigated whether APP instigates reactive astroglios by examining in vitro and in vivo the morphology and function of naive and APP-deficient astrocytes in response to APP and well-established stressors. RESULTS: Overexpression of APP in cultured astrocytes led to remodeling of the intermediate filament network, enhancement of cytokine production, and activation of cellular programs centered around the interferon (IFN) pathway, all signs of reactive astrogliosis. Conversely, APP deletion abrogated remodeling of the intermediate filament network and blunted expression of IFN-stimulated gene products in response to lipopolysaccharide. Following traumatic brain injury (TBI), mouse reactive astrocytes also exhibited an association between APP and IFN, while APP deletion curbed the increase in glial fibrillary acidic protein observed canonically in astrocytes in response to TBI. CONCLUSIONS: The APP thus represents a candidate molecular inducer and regulator of reactive astrogliosis. This finding has implications for understanding pathophysiology of neurodegenerative and other diseases of the nervous system characterized by reactive astrogliosis and opens potential new therapeutic avenues targeting APP and its pathways to modulate reactive astrogliosis.
Keywords: Amyloid beta-Protein Precursor; myši; astrocyty; myši inbrední C57BL; Mice, Inbred C57BL; Gliosis; kultivované buňky; Animals; Mice, Knockout; glióza; Astrocytes; Brain Injuries, Traumatic; Mice; zvířata; traumatické poranění mozku; Cells, Cultured; amyloidový prekurzorový protein beta; myši knockoutované